Pengaruh Perbandingan Komposisi Media Tanah Pasca Tambang dengan Pembenah Tanah Faba terhadap Kemasaman Tanah dan Pertumbuhan Land Cover Crop (Pueraria javanicum) - Nida Khofiyya; Nunung Sondari; Linlin Parlinah (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2021)
The higher the use of coal in the industry, the higher the waste produced. This causes environmental problems such as air, soil, water pollution and a decrease in the quality of ecosystems and public health in industrial environments. For this reason, it is necessary to make efforts to utilize coal waste so that unwanted things do not occur, one of which is by using coal ash waste as a soil repairer to improve soil quality in post-mining land. This experiment was carried at the Faculty of Agriculture screenhouse, Winaya Mukti University, Tanjungsari, Sumedang Regency on the altitude of 850 M above sea level. The trial period is from Jully to August 2020. The experiment aims to determine the effect of comparisons of post-mining soil media composition with Faba fixer on the value of growth of Pueraria javanicum plants. The experimental design used was a randomized block design (RBD) which consisted of five treatments and was repeated five times. Treatment is the ratio of Fla Ash Bottom Ash soil repairer and post-mining soil with the following dosages; A = 100% post-mining soil, B = 25% Faba soil repairer + 75% post-mining soil, C = 50% Faba soil repairer + 50% post-mining soil, D = 75% Faba soil repairer + 25% post-mining soil, E = 100% Faba soil repairer. The results showed that treatment C (50% Faba soil repairer + 50% soil) had a good effect on plant height and shoot wet weight, treatment D (75% Faba soil repairer + 25% soil) had a good effect on the number of leaves, root length, number of effective nodules, and root wet weight of Pueraria javanicum plants.